Cerebral MR in ophthalmoplegia plus. - Leutner, C; Layer, G; Zierz, S; Solymosi, L; Dewes, W; Reiser, M (American Journal of Neuroradiology, 1994)
PURPOSE To evaluate MR patterns in ophthalmoplegia plus and correlate them with clinical symptoms. METHODS MR was performed on a 1.5-T whole-body scanner with T2-weighted gradient-echo and spin-echo images. The retrospective analysis included 19 patients with clinically established diagnoses of ophthalmoplegia plus. RESULTS Two types of cerebral MR abnormalities were found in ophthalmoplegia plus: brain atrophy and hyperintensities restricted to the white matter and basal ganglia, which appeared as either focal or diffuse areas of high signal intensity and were of strictly supratentorial location. No specific distribution was found. These findings differ markedly from infarction-like lesions found in mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes. CONCLUSIONS MR is sensitive for the detection of central nervous system involvement in ophthalmoplegia plus, but findings are nonspecific. However, cerebral MR in ophthalmoplegia plus is different from other mitochondrial encephalomyopathies and underlines the clinical differentiation of mitochondrial encephalomyopathies.